2018
DOI: 10.5539/jps.v7n2p29
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aroma Gene and its Application in Rice Genetics and Breeding

Abstract: Rice (Oryza sativa L.) is one of the most important food crops in the world, and the staple food for more than half of the world's population. Along with the sustained development of living standards, people's demand for high quality rice is increasing. As one of the types of cultivated rice, aromatic rice is preferred by most of the consumers because of its agreeable scent. With the rapid development of rice functional genomics and sequencing technology, great progress has been made in understanding the aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Peng et al [26] consequently asserted that the odorous characteristics of the rice grain can also be regulated by other genes or introns. In a study by Kumar et al…”
Section: Resultsmentioning
confidence: 99%
“…Peng et al [26] consequently asserted that the odorous characteristics of the rice grain can also be regulated by other genes or introns. In a study by Kumar et al…”
Section: Resultsmentioning
confidence: 99%
“…This task can be achieved more easily if a DNA marker that is tightly linked with fragrance is used in marker assisted breeding (MAB) programs. There are many reports of successful use of fragrant allele specific markers in MAB (Shi et al ., 2008; Hashemi et al ., 2015; He and Park, 2015 and Peng et al ., 2018). We tested local germplasm to detect the badh2.1 fragrant allele using the frg (Bradbury et al ., 2005b) DNA marker.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are necessary to observe the impact of the variations in intron regions observed in this study on fragrance.Breeding of fragrant rice consumes much time and needs skilled labor for the evaluation of fragrance. This task can be achieved more easily if a DNA marker that is tightly linked withHe et al, 2015 andPeng et al, 2018). We tested local germplasm to detect the badh2.1 fragrant allele using the frg(Bradbury et al, 2005b) DNA marker.…”
mentioning
confidence: 99%
“…Previous studies indicated the presence of more than 300 aromatic compounds in aromatic rice (Petrov et al, 1996; Widjaja et al, 1996; Wakte et al, 2017). Among them, 2‐acetyl‐1‐pyrroline (2‐AP) is a key aromatic compound present in aromatic cultivars, especially basmati and jasmine (Lorieux et al, 1996; Jezussek et al, 2002; Sakthivel et al, 2009; Peng et al, 2018). It produces a popcorn‐like and nutty pleasant aroma while cooking rice, and breeders are trying to engineer high 2‐AP‐containing cultivars.…”
Section: Introductionmentioning
confidence: 99%